Stiffness based in-situ assessment of static recrystallization kinetics for cold-rolled aluminum alloys - Thomas Obermayer; Christian Krempaszky; Ewald Werner (Materials & Design)
Static recrystallization (SRX) plays a crucial role in the processing of cold-rolled aluminum alloys, as it strongly affects key material properties and occurs during various heat treatments along the processing route. However, the characterization of SRX kinetics by established methods is costly and complex. The analysis of the relation between the recrystallization kinetics and the influence of alloying elements, dislocation density and temperature is elaboratory. To overcome this issue, a novel approach is introduced, allowing to assess the recrystallization kinetics from the evolution of the material stiffness measured by the impulse excitation technique (IET) at remarkably high efficiency. Due to the formation of recrystallized grains, the orientation distribution of the polycrystal changes. Consequently, the anisotropic elastic behavior on macroscopic scale changes, which is reflected in the macroscopic elastic properties. Absolute changes in directional Young's moduli between 0.5 GPa and 2.0 GPa during annealing processes up to 70 h are observed via in-situ IET measurements at high accuracy, allowing to characterize the recrystallization kinetics. The proposed method is exemplarily applied to AA1050 processed by cold rolling. Complementary analyses by applying electron backscatter diffraction (EBSD) or by analyzing the evolution of the yield strength are conducted to verify the described method.